Pengaruh Implementasi Kurikulum Merdeka Terhadap Minat Belajar Siswa SMA Negeri 3 Ambon - Kalsum Hasna Noya; Susan Evelin Manakane; Dwi Partini (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Education plays a vital role in improving the quality of human resources, with the curriculum serving as a key guideline. The Merdeka Curriculum is a new policy that provides flexibility in learning to suit students' needs better. This study aims to analyze the influence of implementing the Merdeka Curriculum on students' learning interests at SMA Negeri 3 Ambon. This study employed a quantitative approach by distributing structured questionnaires to 30 randomly selected 10th and 11th-grade students at SMA Negeri 3 Ambon to gather relevant and measurable data. The data were analyzed using simple linear regression. The results show that implementing the Merdeka Curriculum positively and significantly affects students' learning interests, with a regression coefficient of 0.590 and a significance value of 0.000. It indicates that flexible, project-based, student-centered learning can increase student engagement. However, the success of its implementation depends on teacher readiness, availability of learning facilities, and teaching strategies. These findings offer practical implications for schools to optimize the curriculum through teacher training, technology use, and increased student participation to create a more interactive and innovative learning. environment